'Abandoned Women': Transnational Marriages and Gendered Legal Citizens. Issue 100 (3rd April 2019) - Roy, Anupama; Anitha, Sundari; Yalamarty, Harshita
ABSTRACT: Abandonment of women in transnational marriages can be understood in the context of specific social milieus of community and kinship relations and legal jurisdictions associated with specific cultures of law. As a sociological-legal category that dismantles the myth of 'flexible citizenship' in transnational migration, abandonment must be seen in an experiential matrix constituted by the graded/differentiated diaspora, legal frameworks, and institutional structures, which frame the gendered citizen. This article reads stories of abandonment in legal documents where testimonies are mediated by legal practitioners for ameliorative justice through the court, in tandem with personal narratives of abandonment as reported to the authors. Through this reading, the article explores the way particular narratives of personal hurt and 'personal/private' identity – drawing from membership in the family and community – relate with the public identity of the legal citizen, the public governance of marriage by the protective/paternal state, and the 'promise of happiness' in marriage.